Third Five Year Plan Half-Yearly Progress Report 1962-63 Government of Rajasthan - Planning Commission (Planning Commission, 1962)
The allotment for the year 1962-63, the Second year of the Third Five Year Flan, was 38.34 crore or 16,25 per cent of the total plan provision of the State, as against an allotment of Rs. 34.00 crore or 14.40 per cent of the plan provision draft the last year. Thus over the too yearn, 1961—62 and 1962-63, 30.65 per cent of the plan provision was earmarked to be spent, while for the subsequent three years, 69,35 per cent of the pro- posed development out-lay of 23,6 crore remained to be spent.
Directorate of Economics and Statistics, Rajasthan